OceanEddiesToolbox - Complementary Matlab Toolbox to the Faghmous et al. 2015 eddy tracking software ... - Patel, Ramkrushnbhai Shaileshbhai (Zenodo, 2023)
The OceanEddies toolbox contains assortments of scripts and function to complement the Faghmous et al. 2015 eddy tracking software. This toolbox is developed for MATLAB. The included ReadMe.md file contains all the details regarding scripts and functions. If you find a bug or have a comment on the code, please create an issue on GitHub (https://github.com/rampatels/OceanEddiesToolbox). ... : {"references": ["Faghmous, J. H., et al. (2015) A daily global mesoscale ocean eddy dataset from satellite altimetry. Scientific data, (https://www.nature.com/articles/sdata201528 )", "Patel, R. S., (2021) Physical and biogeochemical structure of Southern Ocean eddies. University Of Tasmania, (https://doi.org/10.25959/100.00038437)"]} ...